Development and validation of new analytical methods using sea urchin embryo bioassay to evaluate dredged marine sediments. (1st March 2021) - Bonaventura, Rosa; Zito, Francesca; Morroni, Lorenzo; Pellegrini, David; Regoli, Francesco; Pinsino, Annalisa
Abstract: Management of dredged materials disposal is regulated by several environmental normative requirements, and it is often supported by the integration of chemical data with ecotoxicological characterization. The reliability of a bioassay to assess the potential toxicity of dredged sediments requires the selection of quality criteria that should be based on simple analytical methods and easily understandable hazard for politicians and environmental managers. The sea urchin embryo-toxicity bioassay is considered an essential component for evaluating the quality of sediments in harbour areas but its use, when based exclusively on the observation of normal vs. abnormal embryos, may alter the interpretation of the results, overestimating the risk assessment. To improve the reliability of this assay in establishing a causative relationship between quality of sediments and sea urchin embryonic development, here we developed and validated three Integrative Toxicity Indexes (ITI 2.0, ITI 3.0, ITI 4.0), modifying the already-known ITI (here ITI 1.0). Based on this aim, we used Taranto harbour as a model pilot-study to compare results to those obtained from standard criteria. Among the tested indexes, the ITI 4.0, discriminating strictly developmental delay and morphological defects from fertilized egg to gastrula stage, resulted in the most promising. Highlights: Paracentrotus lividus embryo bioassay was used to evaluate dredged marine sediments. The harbour of Taranto was chosen as a model pilot-study for sediment evaluation. New Integrative Toxicity Indices was developed and validated to improve the reliability of the sea urchin embryo assay. ITI 4.0 weighted developmental delay and malformations in the most balanced way. ITI 4.0 resulted in a promising tool in the quality assessment of dredged sediments.